Transformational Leadership Model of Madrasah Principals in Improving Student Academic Achievement at Nahdlatul Ulama Elementary Madrasah (MI.NU) in Tarakan City - Irmawati (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the transformational leadership model of madrasah principals in improving student academic achievement at the Nahdlatul Ulama Elementary Madrasah in Tarakan City. The focus of the study includes the implementation of transformational leadership applied by madrasah principals and the strategies used to achieve excellent student academic achievement. The study used a qualitative approach with a case study design. Data collection was conducted through observation, in-depth interviews, and documentation studies involving madrasah principals, teachers, education staff, students, and parents. The results show that the implementation of transformational leadership by madrasah principals is manifested through four main dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Madrasah principals act as role models, motivators, innovators, and facilitators in creating an achievement-oriented academic quality culture. The strategies implemented include building a shared vision, strengthening teacher competencies, developing superior academic programs, implementing a continuous monitoring and evaluation system, strengthening partnerships with parents, and providing awards to outstanding students. These implementations and strategies have been proven to improve the quality of learning, student learning motivation, as well as academic achievement and learning outcomes..